Modeling and Analysis of Solar Photovoltaic Assisted Electrolyzer-Polymer Electrolyte Membrane Fuel Cell For Running a Hospital in Remote Area in Kolkata, India - Kamaljyoti Talukdar (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
The present work consists of the modeling and analysis of solar photovoltaic panels integrated with electrolyzer bank and Polymer Electrolyte Membrane (PEM) fuel cell stacks for running different appliances of a hospital located in Kolkata for different climatic conditions. Electric power is generated by an array of solar photovoltaic modules. Excess energy after meeting the requirements of the hospital during peak sunshine hours is supplied to an electrolyzer bank to generate hydrogen gas, which is consumed by the PEM fuel cell stack to support the power requirement during the energy deficit hours. The study reveals that 875 solar photovoltaic modules in parallel each having 2 modules in series of Central Electronics Limited Make PM 150 with a 178.537 kW electrolyzer and 27 PEM fuel cell stacks, each of 382.372 W, can support the energy requirement of a 200 lights (100 W each), 4 pumps (2 kW each), 120 fans(65 W each) and 5 refrigerators (2 kW each)system operated for 16 hours, 2 hours,15 hours and 24 hours respectively. 123 solar photovoltaic modules in parallel each having 2 modules in series of Central Electronics Limited Make PM 150 is needed to run the gas compressor for storing hydrogen in the cylinder during sunshine hours. Article History: Received Feb 5th 2017; Received in revised form June 2nd 2017; Accepted June 28th 2017; Available onlineHow to Cite This Article: Talukdar, K. (2017). Modeling and Analysis of Solar Photovoltaic Assisted Electrolyzer-Polymer Electrolyte Membrane Fuel Cell For Running a Hospital in Remote Area in Kolkata,India. International Journal of Renewable Energy Development, 6(2), 181-191.https://dx.doi.org/10.14710/ijred.6.2.181-191